Satire against Hypocrisy in “The Alchemist” - Shoyimqulova Mahzuna Shavkatovna (Proceedings of The ICECRS, 2019)
This paper investigates major points of the Satire against Hypocrisy. On this case the Alchemist were learned and discussed. Satire is a genre of literature in which vices, follies, abuses, and shortcomings are held up to ridicule, drawing reader’s or the audience’s attention to a particular or wider issues in society, with the intent of shaming individuals, institutions, governments, or society as a whole into improvement. Instead of giving helpful advises, the satirist focus on what is wrong and make fun of selfish, mean-spirited people, hoping we will see these qualities in ourselves or people around us and change